Lignans from the Stem of Styrax japonica - Wu, Na; Wang, Lan; Chzn, Yong-Kuang; Liao, Zhen; Yang, Guang-Yu; Hu, Qiu-Fen (Asian Journal of Chemistry, 2010)
A new lignan (Styrlignan A), together with four known lignans, were isolated from the steam of Styrax japonica (Styracaceae). Their structures were determined by means of HRESIMS, extensive 1D and 2D NMR spectroscopic studies and chemical evidence. The anti HIV-1 activity of Styrlignan A was also evaluated and it shows an anti HIV-1 activity with a TI (therapeutic index) above 38.5.